Literary correspondence: letters and emails in Caribbean writing. Issue 1 (November 2018) - Campa, Marta Fernández
Abstract : This article explores the role of correspondence (and literary archives in general) in illuminating central aspects of Caribbean literary culture and authors' work, with a consideration of the challenges and the need to preserve email correspondence for archives in the future. It aims to demonstrate how the correspondence of a wide range of authors embedded in various literary archives has the potential to deepen our knowledge and sense of the making of Caribbean literary culture and history.